Danes’ attitudes towards climate taxes on air travel and beef - Hedegaard, Troels Fage (Politica, 2022)
Climate taxes are among the most important political tools in the green transition. In Denmark, debates about this often focus on air travel and beef. The study is based on a survey collected after the 2019 national election and shows that there is great support for a climate tax on air travel but not on beef. Moreover, the study shows that support varies across age groups, income, education, and political trust. The effect of these explanations varies between climate taxes on air travel and beef.